DIGITALISATION OF THE WORK OF THE DEAN’S OFFICES OF HIGHER EDUCATION INSTITUTIONS AND PROBLEMS OF ITS IMPLEMENTATION - Самойленко, Олена; Семенов, Антон (SWorldJournal, 2025)
The article is devoted to the features of implementing innovative approaches to the management of universities and faculties. The article considers the main systems used to digitize the work of the dean’s office, their advantages and disadvantages, in par